OPTIMALISASI KONTEN JURNALISTIK MELALUI PENULISAN BERBASIS SEO (SEARCH ENGINE OPTIMIZATION) BAGI REDAKSI AL-MASHALIH DI MAN BONDOWOSO - Dina Fitria Hasanah; Siti Mutmainah; Anita Widjajanti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The transition of Al-Mashalih, the educational magazine of MAN Bondowoso, from a physical format to a digital platform demands that its journalists adopt writing techniques suited to online media, particularly the use of Search Engine Optimization (SEO) to increase content visibility. This community service program provided SEO-based writing training to enhance young journalists’ skills in creating informative and engaging articles optimized for search engines. The program included preparation of training materials, participant needs analysis, delivery of SEO theory, hands-on writing practice, and guided feedback sessions. As a result, participants showed improved ability to produce SEO-friendly articles, contributing to higher content quality and better search engine rankings for Al-Mashalih.